Maturity Measurement of Information and Communication Technology Infrastructure Governance and Management in Mojokerto Regency using Cobit 2019 - Muzakir Adi Susandik; Raden Venantius Hari Ginardi (Publikasi Indonesia, 2025)
Abstract. In the current era of digital transformation, local governments are responsible for providing convenient and fast services to the public. Therefore, adequate preparation of information and communication technology (ICT) infrastructure is crucial to supporting the digital transformation initiated by the Mojokerto Regency government. The Mojokerto Regency Communications and Information Technology Office (Diskominfo) faces several challenges related to managing ICT service infrastructure. These include the uneven distribution of ICT network infrastructure across all service departments and the lack of integration of data services within Diskominfo's data center. The purpose of this study is to examine the current situation and provide recommendations regarding the stages and priorities for managing ICT network infrastructure at Diskominfo. Therefore, an appropriate method is needed to identify the condition of the ICT infrastructure and evaluate its performance achievements using the COBIT 2019 framework. The research was conducted through problem identification, stakeholder discussions, data collection, data analysis, and reporting. The results of this study are a measurement of the maturity of ICT infrastructure governance and management, based on the COBIT 2019 framework with objective domain processes BAI02 Managed Requirements Definition, BAI03 Managed Solutions Identification and Build, BAI06 Managed IT Changes, and BAI10 Managed Configuration. These recommendations and suggestions can be used to further improve ICT governance and management services in all organizations.